Emotional intelligence in early adolescence: validation dana based on peer ratings and an objective ability-based test - Buško, Vesna (Array, 2013)
The paper presents a part of empirical validation procedures on emotional ntelligence as operationalized by two different assessment methods but derived from the same ability-based conceptualization. The study was conducted on a sample of 180 seven- and eight-grade primary school students. The structure of age and gender differences in EI dimensions was examined by canonical discriminant analysis. Confirmatory factor analyses demonstrated moderate convergence between the performance-based emotion management EI test and peer-rated EI measures. By use of hierarchical regression procedures we tested the relative importance of emotional intelligence variables in explaining sociometric status as a measure of social adjustment in primary school pupils. The results showed that the regression equation including age and sex as general demographic features, GPA as a substitute for a general capacity measure in pupils, and emotional intelligence variables can account for approximately 65% of criterion variance. Peer-rated emotional regulation abilities showed considerable additive contribution to the criterion variance, whereas the role of Emotion management test within the predictor structure examined proved to be practically and statistically insignificant.